Upaya Menurunkan Inkontinensia Urine Dengan Bladder Training Pada Pasien Paraplegia Di RSOP Surakarta - Nur Amin, Wahyu Isro, Fahrun Nur Rosyid, S.Kep., Ns., M.Kes (2016)
Paraplegia patient is a patient who suffered a fracture or a shift of one or more vertebrae resulting in neurological deficit. In addition to a disturbance in the nervous system, also cause interference with the system of limination is urinary incontinence. Urinary incontinence is the inability to hold urine out of the bladder, either conscious or unconscious. From medical records in RSOP Surakarta from January 2016 to April 2016 has increased. The purpose of this study was to determine the development of a decrease in the frequency of urinary incontinence in patients with paraplegia. The method used is the method of Case Study, by sample Ny.S The data collected in this study is to conduct direct observation of patients, interviews with patients and families, see a medical record of the patient, and in collaboration with other health care workers. further analyze data, formulate a diagnosis, intervention, implementation and evaluation. The results of this case study is after doing bladder training nursing actions during 3x24 hours on the problem of urinary incontinence in the expected frequency of urinary ncontinence can be decreased. Bladder training action should be undertaken on a regular basis so that the patient really feel the effects of the practice.